Karakterisasi Nukleotida Daerah Ekson 5 dan 6 Gen LDLR Penduduk Papua - Hamida; Achmad Taher (FMIPA Universitas Papua, 2019)
The diversity shown in tribes in Papua has the potential to produce varying genetic diversity. LDLR gene is a gene coding for LDL receptor proteins (LDL-R) that play a very important role in cholesterol homeostasis. The LDLR gene consists of 18 exons and 17 introns that stretch for 45 kilos of base (kb). . The exon 5 and 6 regions are important structural parts in encoding amino acids and are also ligand binding regions that mediate the interaction between receptors and lipoproteins containing Apo B-100 or Apo E. This study aims to characterize the nucleotides of Papuan populations with different origins. The method used is the polymorphism chain reaction method and sequencing method to find out the sequence of nucleotide bases. The results of the exon 5 and 6 regional nucleotide characterization of LDLR genes from 9 UNIPA students from Papua showed identical results because they had the same number of nucleotides and nucleotide arrangements. The number of nucleotides for exon 5 area is 123 pb, consisting of T = 22.0%, C = 24.4%, G = 30.9%, A = 22.8%, A + T = 44.8% and C + G = 55.3%. For exon 6 area with nucleotide amount of 123 pb, the nucleotide composition is T = 16.3%, C = 26.8%, G = 27.6%, A = 29.3%, A + T = 45.6% and C + G = 54.4%. The same results show that the two regions are conserved.